Record of the Non-native Suckermouth armored catfish hybrid Pterygoplichthys pardalis (Castelnau,1985) x Pterygoplichtys disjunctivus (Weber, 1991) (Siluriformes: Loricariidae) in Honduras - Lardizabal, Claudia C.; Benitez, Edis M.; Matamoros, Wilfredo A. (Zootaxa, 2020)
Loricariidae is the largest catfish family, with over 1000 species and 80 genera (Fricke & Eschmeyer, 2019). Sailfin catfishes of the genus Pterygoplichthys are armored catfishes, native to temperate and tropical areas of South America, especially the Amazon (Wakida-Kusunoki & del Angel, 2011). Two species of this genus (Pterygoplichthys pardalis (Castelanu, 1855) and P. disjunctivus (Weber, 1991)) are naturally distributed in South America along the lower, middle and upper basin of the entire Amazon River (Wakida-Kusunoki & del Angel, 2008). These armored catfishes, typified by the presence of ossified plates through the body, are considered very successful invaders of rivers and lakes outside their natural range. Their invasion success has been attributed to their morphology, behavior and life history. For instance, their ability to withstand droughts and cold weather by using burrows in river and lake banks they can survive in the moist habitat even when water levels decrease below the opening of the burrows, these survival characteristics of harsh conditions enable them to thrive in native and non-native grounds (Burgess 1989; Hoover & Killgore 2004; Nico & Martin 2001; Sandoval-Huerta et al. 2012). Furthermore, their rapid growth during their first years of life, their reproductive traits such as an extended reproductive period, high egg yield (Rueda-Jasso et al. 2013), and the capability of achieving reproductive maturity at smaller size (Wei et al. 2017) allow introduced populations to become abundant in a short period of time.